Efficacy of weekly trastuzumab and paclitaxel in the treatment of women with HER-2/neu overexpressing metastatic breast cancer - Janku, Filip (Radiology and oncology (Ljubljana), 2002)
Purpose. Trastuzumab is known as an active agent in HER2/neu overexpressing metastatic breast cancer. In the prospective study we investigated efficacy, safety and toxicity of trastuzumab and paclitaxel in metastatic breast cancer progressing on previous therapy. Patients and methods. We accrued 17 patients with histologically confirmed breast cancer, Karnofsky performance status at least 60 %, median age 50 (36-66), pretreated with at least two regimens. HER-2/neu expression was tested by HercepTest (r) (DAKO) in all 17 patients. Fifteen specimens were 3+ positive and 2 specimens 2+ positive. All patients except one were pretreated with taxanes. Taxane free interval (TFI) was defined as a time from last taxane administration until the beginning of the study for every enrolled patient. TFI longer than 1 year was found in 7 patients. TFI shorter than 1 year was observed in 9 patients. Trastuzumab was given 4 mg/kg i.v. as a loading dose followed by 2 mg/kg i.v. weekly. Paclitaxel was given 80 mg/m2 i.v. weekly until disease progression or unacceptable toxicity. We assessed the response rate (RR), the time to progression (TTP), the survival (OS) and toxicity. (Abstract truncated at 2000characters)
Keywords: Analiza preživetja; Antagonists and inhibitors; breast; Breast neoplasms; Dojka, novotvorbe; dojke; Drug therapy; Izid zdravljenja; Karnofsky performance status; Karnofskyva ocena sposobnosti; Neoplasm metastasis; Novotvorba, metastaza; novotvorbe; Prospective studies; Prospektivne študije; Proto-oncogene proteins c-erbb-2; Survival analysis; therapy; Treatment outcome; tumor; zdravljenje